Are There Differences in Placental Volume and Uterine Artery Doppler in Pregnancies Resulting From the Transfer of Fresh Versus Frozen-Thawed Embryos Through In Vitro Fertilization. (October 2016) - Rizzo, Giuseppe; Aiello, Elisa; Pietrolucci, Maria Elena; Arduini, Domenico
Objective: To compare uterine artery pulsatility index (PI) and 3-dimensional (3D) placental volume values in first-trimester pregnancies conceived naturally or through in vitro fertilization (IVF) technique using either fresh or cryopreserved embryo and to relate these measurements with preeclampsia (PE) development. Methods: Uterine artery PI and placental volume were measured at 11 + 0 to 13 + 6 weeks of gestation in 266 IVF pregnancies (139 women with fresh embryo and 127 women with frozen-thawed embryo transfer) and in 266 spontaneously conceived pregnancies matched for maternal age. Nulliparous women with singleton pregnancies were recruited. The mean, highest, and lowest uterine artery PI and placental volume values measured were converted to multiples of the expected normal median (MoM) adjusted for gestational age. The MoM values of IVF pregnancies were compared with those of the naturally conceived group and related to PE development. Results: No differences were found in uterine artery PI MoM between the 3 groups. Placental volume was significantly lower than in both IVF groups when compared to the controls (fresh embryo IVF Z = 9.33; P ≤ .0001; frozen-thawed embryos IVF Z = 3.1; P = .04). The IVF pregnancies with fresh embryos showed placental volume MoM values significantly lower than in the frozen-thawed embryo IVF pregnancies ( U = 5.4; P ≤ .0001). In fresh embryo IVF pregnancies developing PE placental volume values resulted lower than in the normotensive ones ( U = 2.11; P = .03), while no differences were found for uterine artery PI values. Conclusion: First-trimester placental volume, as assessed by 3D ultrasound, is reduced in IVF pregnancies, and these differences are more marked in those obtained withfresh embryos than those obtained withcryopreservation . This may explain the better obstetrical and perinatal outcomes occurring with the former technique.